Literature Review: The Effect Of Roa, Roe, And Der On Stock Prices Of Manufacturing Companies On The Idx - Maulana Akmal Malik; Enggar Diah Puspa Arum; Wira Lestari (Cita konsultindo, 2025)
This study aims to analyze the relationship between profitability ratios, represented by Return on Assets (ROA) and Return on Equity (ROE), and stock prices in food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) for the 2018–2024 period. This sector was chosen because it has relatively stable characteristics compared to other sectors and is a key driver of national economic growth. Amid the economic dynamics following the COVID-19 pandemic, many companies face pressure on profits and operational efficiency, which ultimately impacts investors' perceptions of company value in the capital market. Based on signaling theory, financial performance reflected in profitability ratios can be an important signal for investors in assessing a company's prospects. This study uses a quantitative approach with multiple linear regression to examine the relationship between ROA, ROE, and stock prices. Secondary data were obtained from annual financial reports and stock price data of food and beverage subsector companies listed on the IDX during the observation period. Data analysis was conducted using the classical assumption test, the coefficient of determination (R²), and partial (t-test) and simultaneous (F-test) tests to ensure the validity of the research model. The results show that ROE has a positive and significant effect on stock prices, meaning that the higher the return on equity, the greater investor interest in the company's shares. Meanwhile, ROA had no significant effect on stock prices, indicating that asset utilization efficiency is not yet a primary concern for investors in this subsector. This finding supports signaling theory, which states that investors are more responsive to financial ratios that directly reflect shareholder returns than to a company's operational efficiency. The practical implications of this study suggest that management of companies in the food and beverage subsector needs to focus more on increasing shareholder equity value through effective financial strategies, such as earnings management, consistent dividend policies, and capital structure optimization. For investors, the results of this study can serve as a reference in making investment decisions, emphasizing equity-based profitability analysis. From an academic perspective, this research provides originality by examining the relationship between ROA, ROE, and stock prices in the post-pandemic period, focusing on subsectors with defensive characteristics, such as food and beverages. This research also broadens understanding of the role of profitability ratios as financial signals in the context of the Indonesian capital market, which is experiencing economic recovery.